Robust Planning for Hydrogen-Based Multienergy System Considering P2HH and Seasonal Hydrogen Storage - Shufan Wang; Dong Yang; Linglu Zhang; Lingzhi Chenmei (International Transactions on Electrical Energy Systems)
Since renewable energy is rapidly growing in the active distribution networks, the integrated energy system coupled with energy storage is a promising way to address the intermittent issues of renewable sources. This paper proposes an optimal planning model for the hydrogen-based integrated energy system (HIES) considering power to heat and hydrogen (P2HH) and seasonal hydrogen storage (SHS) to take full advantage of multienergy complementarity. To tackle the unstable factors introduced by renewable sources and varying loads, we apply robust optimization and stochastic programming theory to improve the robustness of the planning results. Meanwhile, we also consider the N-1 contingency constraints to make the technology selection, capacity allocation, and economic operation more reliable. The complex constraints resulting from producing two independent binary variables are converted into mixed integer linear constraints, which can be solved effectively using the nested column-and-constraint generation algorithm. Numerical simulation demonstrates the effectiveness of the P2HH and SHS in reducing the total cost of the HIES planning.